The Role of Madrasah Diniyah in Shaping the Religious Character - Sahid, Toto Ahmad; Ali, Moh. (Research Horizon, 2025)
Madrasah diniyah plays a crucial role as a non-formal Islamic educational institution dedicated to nurturing religious values among rural youth. This study seeks to explore the strategies implemented by madrasah diniyah in socializing Islamic values and to analyze their influence on shaping students’ religious character. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and document analysis. The results indicate that madrasah diniyah conducts value socialization through a salafiyah-based diniyah curriculum, classical Islamic text learning, exemplary moral behavior demonstrated by teachers, and student participation in various religious and social activities. These educational strategies contribute significantly to strengthening family-based religiosity, fostering young Islamic leadership, and enhancing community solidarity grounded in Islamic values. This study affirms that madrasah diniyah’s role as a secondary agent of socialization in accordance with Durkheim’s theory of social integration and Bourdieu’s concept of religious habitus. Therefore, the model developed by madrasah diniyah is recommended to be replicated in other rural communities as a practical framework for community-based Islamic education development.